Arthritogenic alphaviruses: epidemiological and clinical perspective on emerging arboviruses - Zaid, Ali; Burt, Felicity J; Liu, Xiang; Poo, Yee Suan; Zandi, Keivan; Suhrbier, Andreas; Weaver, Scott C; Texeira, Mauro M; Mahalingam, Suresh (The Lancet infectious diseases, 2021)
Mosquito-borne viruses, or arboviruses, have been part of the infectious disease landscape for centuries, and are often, but not exclusively, endemic to equatorial and subtropical regions of the world. The past two decades saw the re-emergence of arthritogenic alphaviruses, a genus of arboviruses that includes several members that cause severe arthritic disease. Recent outbreaks further highlight the substantial public health burden caused by these viruses. Arthritogenic alphaviruses are often reported in the context of focused outbreaks in specific regions (eg, Caribbean, southeast Asia, and Indian Ocean) and cause debilitating acute disease that can extend to chronic manifestations for years after infection. These viruses are classified among several antigenic complexes, span a range of hosts and mosquito vectors, and can be distributed along specific geographical locations. In this Review, we highlight key features of alphaviruses that are known to cause arthritic disease in humans and outline the present findings pertaining to classification, immunogenicity, pathogenesis, and experimental approaches aimed at limiting disease manifestations. Although the most prominent alphavirus outbreaks in the past 15 years featured chikungunya virus, and a large body of work has been dedicated to understanding chikungunya disease mechanisms, this Review will instead focus on other arthritogenic alphaviruses that have been identified globally and provide a comprehensive appraisal of present and future research directions.